Morphofunctional Study of Placental Cryoextract Nephroprotective Effect in Acute Renal Failure in Rats - Vaskovych, Artem M.; Repin, Nikolay V.; Marchenko, Larisa N. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):177.